USE OF COMPUTER SIMULATION IN STUDYING CIRCUITS OF DIRECT CURRENT - Savchuk, Varfolomii; Romanetc, Olena (Physical and Mathematical Education, 2023)
Formulation of the problem. Studying and consolidating educational material in physics is based on experiments. The latter are rather difficult to implement in the conditions of distance learning. Modern information technologies allow such implementation. In the article, as an example, the use of computer simulation in the study of a direct current circuit in the conditions of distance learning is considered.Materials and methods. The formulation of the problem and its solution is based on the materials of physics curricula for grades 10-11 of general educational institutions and bachelor's level physics programs for institutions of higher education in physical and technical specialties and specialist 014.08., materials of scientific-pedagogical and scientific-methodical sources, in which issues related to the conducted research are considered. Materials from resources on computer simulations, in particular from the phet interactive simulations site, were also used. The results. The analysis of the materials used determined a complex of experimental works of the physical workshop on electricity, the variability of the tasks in which provided the opportunity to use them in different educational formats (both in senior classes of secondary comprehensive schools and in junior courses of the bachelor's level). Using a computer simulation from the phet interactive simulation site as an example, an educational experiment on the topic "Investigation of direct current, useful power and efficiency of a current source" was considered.Conclusions. The use of interactive simulation when studying the topic "Ohm's law for a complete circle. The power of direct current" allows you to simulate the specified physical experiment and use its results to justify a number of theoretical propositions on the topic being studied. The developed methodological support for the experiment allows its use at various levels of physics education. It is promising to create a complex of laboratory works for various sections of the general physics course, based on the use of computer simulations, and to develop methodological support for their implementation.
Keywords: computer simulations; Phet-simulations; independent work; homework; physical experiment; direct current; useful power